Transmigration of polymorphnuclear neutrophils and monocytes through the human blood-cerebrospinal fluid barrier after bacterial infection in vitro - Steinmann, Ulrike (BioMed Central, 2013)
BACKGROUND: Bacterial invasion through the blood-cerebrospinal fluid barrier (BCSFB) during bacterial meningitis causes secretion of proinflammatory cytokines/chemokines followed by the recruitment of leukocytes into the CNS. In this study, we analyzed the cellular and molecular mechanisms of polymorphonuclear neutrophil (PMN) and monocyte transepithelial transmigration (TM) across the BCSFB after bacterial infection. METHODS: Using an inverted transwell filter system of human choroid plexus papilloma cells (HIBCPP), we studied leukocyte TM rates, the migration route by immunofluorescence, transmission electron microscopy and focused ion beam/scanning electron microscopy, the secretion of cytokines/chemokines by cytokine bead array and posttranslational modification of the signal regulatory protein (SIRP) α via western blot. RESULTS: PMNs showed a significantly increased TM across HIBCPP after infection with wild-type Neisseria meningitidis (MC58). In contrast, a significantly decreased monocyte transmigration rate after bacterial infection of HIBCPP could be observed. Interestingly, in co-culture experiments with PMNs and monocytes, TM of monocytes was significantly enhanced. Analysis of paracellular permeability and transepithelial electrical resistance confirmed an intact barrier function during leukocyte TM. With the help of the different imaging techniques we could provide evidence for para- as well as for transcellular migrating leukocytes. Further analysis of secreted cytokines/chemokines showed a distinct pattern after stimulation and transmigration of PMNs and monocytes. Moreover, the transmembrane glycoprotein SIRPα was deglycosylated in monocytes, but not in PMNs, after bacterial infection. CONCLUSIONS: Our findings demonstrate that PMNs and monoctyes differentially migrate in a human BCSFB model after bacterial infection. Cytokines and chemokines as well as transmembrane proteins such as SIRPα may be involved in this process.